Release studies of undecylenoyl phenylalanine from topical formulations - Anna Olejnik; Aleksandra Glowka; Izabela Nowak (Elsevier, 2018)
The aim of this study was to characterize the stability of new vehicles for the undecylenoyl phenylalanine that is used as skin-lightening agent in the melasma treatment. The purpose of this research was also to analyse the release kinetics of phenylalanine derivative from topical preparations through different synthetic membranes. Topical formulations such as two different macroemulsions, hydrogels (based on carbomer and hydroxyethylcellulose) and microemulsions were characterized in terms of stability by laser diffraction method. Additionally, multiple light scattering assessed the stability of macroemulsions. The release rates of active substance through different membranes (such as Cuprophan, nitrocellulose, cellulose acetate and Strat-M) were determined using enhancer cell. In order to explain the mechanism of release process the results were fitted with different kinetic models. New stable vehicles for Ude-Phe were successfully obtained. The results proved that the membrane structure had the influence on the release rate of undecylenoyl phenylalanine. The slowest release rate of Ude-Phe was observed when Strat-M membrane was applied. The highest amount of active substance was released from the hydrogel based on carbomer. The release of undecylenoyl phenylalanine from both macroemulsions and hydrogel based on hydroxyethylcellulose followed the Higuchi model. Whereas the release results of Ude-Phe from both microemulsion-based hydrogels and carbomer hydrogel can be described by using Korsmeyer-Peppas model. Hydrogels and microemulsion-based hydrogels could be recommended as proper vehicles for the derivative of phenylalanine. Keywords: Semi-solid formulations, Release studies, Synthetic membranes, Stability, Amino acid derivative